Successional Pattern and Plant Species Diversity in Terai-Bhabher Landscape in North-Central Uttar Pradesh, India - Misra, V.K. (Indian Forester, 2013)
The vegetation of study area is broadly divided into four physiognomic units viz. forest, secondary forest, grasslands and artificial vegetation. Shannon's diversity index, species richness and species composition of the vegetation of study area has been worked out. A total of 944 plant species belonging to 510 genera and 130 families are reported from the study area. The diversity of the study area is 4.292. Plant species diversity in different concrete plant communities has also been determined. The species diversity of total forested area is 4.115. Among different forest stands sal forest exhibit maximum species diversity (H' = 3.530). The grasslands as a whole showed high diversity (H'=4.198) with maximum contribution of erect annual herbs. Mesic grassland show maximum species diversity (H' = 3.907) among different grassland communities. Shrubs contribute maximum to the species diversity in degenerated forest. Climbers contribute very less to the species diversity of all the communities. The study area harbours some of the rare and threatened species needing effective conservation measures. An attempt has been made to deduce the successional pattern and affinities among different plant communities.